THE LEGAL IMPLICATION OF COMPULSORY LICENCE PHARMACEUTICAL PRODUCTS IN THE TRIPs AGREEMENT TO THE PROTECTION OF THE RIGHT TO HEALTH IN DEVELOPING COUNTRIES - Sri Wartini (Jurnal Dinamika Hukum, 2018)
Compulsory license of pharmaceutical products in the Trade Related Aspects of Intellectual Property Rights (TRIPs) Agreement attempts to balance the interest of patent holders and The right to health. The access of medicines in developing countries for the epidemic diseases, such as, HIV/AIDS  medicine is crucial to  protect The right to health. The objective of the research is to analyze comprehensively the legal implication  of compulsory license for the pharmaceutical product to the protection of The right to health in developing countries. It is  a normative juridical research by applying conceptual and  comparative approaches. The results of the research  shows that: first, the implementation of compulsory licence is in accordance with the international human right law: second, the legal implication of the compulsory license  causes the adoption of policy and regulations regarding the protection of the right to health in developing countries, such as Indonesia, Malaysia, Brazil, India and  South Africa.  Keywords : Compulsory license, pharmaceutical products, legal implication and The right to health